Peripapillary retinal nerve fibre layer thinning, perfusion changes and optic neuropathy in carriers of Leber hereditary optic neuropathy-associated mitochondrial variants - Paul F Kenna; Kirk A J Stephenson; Lorraine Cassidy; Clare Quigley (BMJ Open Ophthalmology)
Background We investigated Leber hereditary optic neuropathy (LHON) families for variation in peripapillary retinal nerve fibre layer thickness and perfusion, and associated optic nerve dysfunction.Method A group of LHON-affected patients (n=12) and their asymptomatic maternal relatives (n=16) underwent examination including visual acuity (VA), visual-evoked-potential and optic nerve imaging including optical coherence tomography (OCT) and OCT angiography of the peripapillary retinal nerve fibre layer (RNFL). A control sample was also examined (n=10). The software imageJ was used to measure perfusion by assessing vessel density (VD), and statistical software ‘R’ was used to analyse data.Results The LHON-affected group (n=12) had significantly reduced peripapillary VD (median 7.9%, p=0.046). Overall, the LHON asymptomatic relatives (n=16) had no significant change in peripapillary VD (p=0.166), though three eyes had VD which fell below the derived normal range at 6% each, with variable VA from normal to blindness; LogMAR median 0, range 0–2.4. In contrast, RNFL thickness was significantly reduced in the LHON-affected group (median 51 µm, p=0.003), and in asymptomatic relatives (median 90 µm, p=0.01), compared with controls (median 101 µm). RNFL thinning had greater specificity compared with reduced perfusion for optic nerve dysfunction in asymptomatic carriers (92% vs 66%).Conclusion Overall, reduced peripapillary retinal nerve fibre layer perfusion was observed in those affected by LHON but was not reduced in their asymptomatic relatives, unlike RNFL thinning which was significantly reduced in both groups versus controls. The presence of RNFL changes was associated with signs of optic neuropathy in asymptomatic relatives.